Peran Guru dan Lembaga Sekolah dalam Meminimalisir Perilaku Bulliying di MTs Tauhidiyah 2 Sengeten Gondang Bojonegoro - Muhamad Ibnu Syaifuddin; Retno Nuzilatus shoimah; Khotimatus Sholikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the role of teachers and school institutions in minimizing bullying behavior at MTs Tauhidiyah 2 Senganten Gondang Bojonegoro. Bullying cases in schools, especially verbal and social bullying, are still ongoing problems and affect students' psychological well-being and academic achievement. Design/methods/approach – This study uses a qualitative approach with a case study method at MTS Tauhidiyah 2 Senganten Gondang Bojonegoro. Data collection was carried out through observation, documentation, and in-depth interviews involving teachers, principals, and students. The data were then analyzed using data reduction techniques, data presentation, and drawing conclusions, with triangulation to ensure its validity. The results of the study show that teachers play an important role as mentors and role models, providing motivation, emotional support, and character guidance to students. Meanwhile, school institutions contribute through policy development, character education, psychological services, and creating a positive school culture. Strong leadership from the principal also plays an important role in the psychological well-being of students which will encourage all elements of the school to work synergistically in creating a bullying-free environment. Strong moral leadership from the principal will ensure that all policies are not only implemented administratively, but truly become part of the school culture. This study was limited to a single case in one school, which may not be fully representative of the broader educational context. However, the findings highlight the need for systemic and collaborative efforts involving all school stakeholders in bullying prevention. Further research could be expanded to multi-site studies or develop intervention models that integrate families and the broader community.